Repurposing risperidone as an anti-angiogenic agent for triple-negative breast cancer: a computational to in ovo investigation - Jain, Anisha; Motatis, Anil Kumar Belagal; Dharmashekar, Chandan; Shreevatsa, Bhargav; VS, Siddesh; Srinivas, Monisha; Srinivasa, Sudhanva Muddenahalli; P, Ashwini; Prasad, M. N. Nagendra; Rosell, Rafael; Codony-Servat, Jordi; Rangappa, Shobith; et al. (Frontiers in Oncology, 2025)
IntroductionTriple-negative breast cancer (TNBC) is a challenging subtype of breast cancer to treat because it lacks the expression of progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor 2 (HER2). A significant majority of deaths related to cancer are caused by tumor metastasis and angiogenesis. Vascular endothelial growth factor receptor 2 (VEGFR2) plays a significant role in angiogenesis. Instead of developing new molecules, drug repurposing, also known as repositioning, seeks innovative uses for outdated drugs or those that fail due to ineffectiveness.MethodsIn this study, we performed high-throughput virtual screening of FDA approved drug library taken from Enamine bioactive collection targeting VEGFR proteins, and the top hit compounds analyzed by molecular dynamics simulations and MM-GBSA were considered for further in vitro analyses against human breast cancer cells, MDA-MB-231 and MDA-MB-468 cells followed by in ovo assay using the Chorioallantoic Membrane (CAM) model.ResultsThe results revealed that risperidone was effective against triple-negative breast cancer, with IC50 values ranging from 46.53 to 49.76 µM. The findings of our study demonstrated that risperidone, an antipsychotic drug, could successfully inhibit human breast cancer cells in silico, in vitro and in ovo.DiscussionWe could prove that a structure-based drug repurposing approach is an effective strategy to produce a promising antiangiogenic repurposed drug that could also inhibit VEGFR2 in breast cancer. Although risperidone showed modest potency, its clinical availability and repurposing potential support further evaluation in preclinical and clinical settings.